To evaluate the equation \( y = 2(5 - 3x) - 6 + 9x \) for \( x = 3 \) and \( x = 11 \), we will substitute these values of \( x \) into the equation and simplify.
Step 1: Evaluate for \( x = 3 \)
-
Substitute \( x = 3 \) into the equation: \[ y = 2(5 - 3(3)) - 6 + 9(3) \]
-
Calculate \( 3(3) \): \[ 3(3) = 9 \]
-
Substitute into the equation: \[ y = 2(5 - 9) - 6 + 27 \]
-
Calculate \( 5 - 9 \): \[ 5 - 9 = -4 \]
-
Substitute into the equation: \[ y = 2(-4) - 6 + 27 \]
-
Calculate \( 2(-4) \): \[ 2(-4) = -8 \]
-
Substitute: \[ y = -8 - 6 + 27 \]
-
Calculate \( -8 - 6 \): \[ -8 - 6 = -14 \]
-
Substitute: \[ y = -14 + 27 \]
-
Finally, calculate: \[ -14 + 27 = 13 \]
So, when \( x = 3 \), \( y = 13 \).
Step 2: Evaluate for \( x = 11 \)
-
Substitute \( x = 11 \) into the equation: \[ y = 2(5 - 3(11)) - 6 + 9(11) \]
-
Calculate \( 3(11) \): \[ 3(11) = 33 \]
-
Substitute into the equation: \[ y = 2(5 - 33) - 6 + 99 \]
-
Calculate \( 5 - 33 \): \[ 5 - 33 = -28 \]
-
Substitute: \[ y = 2(-28) - 6 + 99 \]
-
Calculate \( 2(-28) \): \[ 2(-28) = -56 \]
-
Substitute: \[ y = -56 - 6 + 99 \]
-
Calculate \( -56 - 6 \): \[ -56 - 6 = -62 \]
-
Substitute: \[ y = -62 + 99 \]
-
Finally, calculate: \[ -62 + 99 = 37 \]
So, when \( x = 11 \), \( y = 37 \).
Summary:
- When \( x = 3 \), \( y = 13 \).
- When \( x = 11 \), \( y = 37 \).